Relating In Vitro Neutralization Level and Protection in the CVnCoV (CUREVAC) Trial. (1st February 2022) - Cromer, Deborah; Reynaldi, Arnold; Steain, Megan; Triccas, James A; Davenport, Miles P; Khoury, David S
Abstract: The vaccine candidate CVnCoV (CUREVAC) showed surprisingly low efficacy in a recent phase 3 trial compared with other messenger RNA (mRNA) vaccines. Here we show that the low efficacy follows from the dose used and the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants and is predicted by the neutralizing antibody response induced by the vaccine.